The Association of CYP2D6*4 and POR*28 Polymorphisms on Mirtazapine Plasma Level in Subjects with Major Depressive Disorder and Anxiety Disorders - Ozdemir, Fezile; Dural, Emrah; Baskak, Nilay S.; Kır, Yaĝmur; Baskak, Bora; Suzen, Halt S. (Combinatorial Chemistry & High Throughput Screening, 2020)
Aims and Objective: The plasma level of mirtazapine (MIR) varies between individuals primarily depending on the differences in metabolism during pharmacotherapy. CYP2D6 takes the role as a major enzyme in MIR metabolism and POR enzyme donates an electron to CYP2D6 for its activity. Single nucleotide polymorphisms in the genes encoding pharmacokinetic enzymes may cause changes in enzyme activity, leading to differences in metabolism of the drug. Our aim was to assess the influence of CYP2D6*4 and POR*28 polymorphisms on MIR plasma levels in Turkish psychiatric patients. Materials and Methods: The association between genetic variations and plasma level of MIR was investigated on 54 patients. CYP2D6*4 and POR*28 polymorphisms were analysed using Polymerase Chain Reaction- Restriction Fragment Length Polymorphism (PCR-RFLP) and plasma MIR levels were measured using HPLC. Results: Allele frequencies of CYP2D6*4 and POR*28 were 0.11 and 0.39, respectively in the study population. The results showed that CYP2D6*4 allele carriers have higher C/D MIR levels while POR*28 allele carriers have lower C/D MIR levels. Combined genotype analyses also revealed that individuals with CYP2D6*1/*1 - POR*28/*28 genotype have a statistically lower C/D MIR level (0.95 ng/ml/dose) when compared with individuals with CYP2D6*1/*1 - POR*1/*1 genotype (1.52 ng/ml/dose). Conclusion: Our results indicate that CYP2D6*4 and POR*28 polymorphisms may have a potential in the explanation of differences in plasma levels in MIR treated psychiatric patients. A combination of these variations may be beneficial in increasing drug response and decreasing adverse drug reactions in MIR psychopharmacotherapy.
Keywords: POR*28